2021
DOI: 10.1002/slct.202003731
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1,2‐Disubstituted Imidazole Derivatives as Potent Inhibitors of Mycobacterium tuberculosis and Their In Silico Studies

Abstract: A multi‐step synthetic protocol was employed to accomplish the synthesis of (2Z)‐2‐((E)‐4‐(benzylideneamino)phenyl)‐3‐(1‐methyl‐1H‐imidazol‐2‐yl)acrylonitrile derivatives. The title compounds were screened for antitubercular activity. Amongst them, three of the compounds appeared promising with a MIC value 0.2 to 0.4 μg/mL whereas the other compounds have also exhibited lower MIC than the standards. Docking study was performed to check their binding interaction and to deduce the possible mechanism of action in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The results showed that 72 , 73 , and 74 (Figure 14) had excellent MIC values in the range of 0.2–0.4 μg/ml without any toxicity to normal human cells. [ 151 ]…”
Section: Biological Activities Of Acrylonitrilesmentioning
confidence: 99%
“…The results showed that 72 , 73 , and 74 (Figure 14) had excellent MIC values in the range of 0.2–0.4 μg/ml without any toxicity to normal human cells. [ 151 ]…”
Section: Biological Activities Of Acrylonitrilesmentioning
confidence: 99%
“…Purines consist of a six-membered pyrimidine ring fused to a five-membered imidazole ring, which is the most broadly occurring nitrogen-containing heterocycle in nature. Imidazoles are significant on the grounds that their ChemistrySelect biological activity among their isomer, especially the imidazole had a broad range of biological potency including antimicrobial, [28][29][30] antituberculosis, [31] antioxidant, [32] antiinflammatory, [33,34] antiproliferative, [35,36] antitumor, [37,38] antiviral, [39] antipyretic, [40] anti-HIV-1, [41] antidepressant, [42] antihypertensive, [43] anticancer, [44] and antifungal activity. [45] These applications of imidazole led to the recent development of drugs and are regarded to be a potential candidate for pharmacological and therapeutic fields.…”
Section: Structure Features Of Imidazolementioning
confidence: 99%
“…Imidazole derivatives are important and famous heterocyclic compound which shows the general and key structure of features of a variety of medicinal Pharmaceutical and natural products. Essential and synthetic imidazole derivatives occupy the main place among pharmaceutically and medicinally important compounds due to their different interesting and widespread medicinal Pharmaceutical and biological activity such as anti-oxidant [1][2] , antiviral [3][4] , anti-cancer [5][6] , anti-inflammatory [7][8] , antituberculosis [9][10] , anti-bacterial [11][12] , antifungal [13][14] , anti-diabetic [15][16] , anti-microbial [17][18] , anticonvulsant 19 , cytotoxic [20][21] , antiproliferative 22 , anticandidal 23 , antiamoebic 24 activity, etc.…”
Section: Introductionmentioning
confidence: 99%